(untitled) (International Journal of Mathematics and Physics, 2012)
We perform experiments with 72 electronic limit-cycle oscillators, globally coupled via a linear or nonlinear feedback loop. While in the linear case we observe standard Kuramoto-like synchronization transition, in the nonlinear case, with increase of the coupling strength, we first observe a transition to full synchrony and then a desynchronization transition to quasiperiodic state. In this state the ensemble remains, however, coherent so that the mean field is non-zero, but mean field frequency is large than frequencies of all oscillators. Next, we analyze common periodic forcing of the linearly or nonlinearly coupled ensemble and demonstrate regimes when the mean field is entrained by the force whereas the oscillators are not.